Toward a Theory of Human Resource Value in Formal Organization. - Flamholtz, Eric (The Accounting Review, 1972)
The article presents information on first step toward a theory of human resource value in formal organizations. This theory seems to have relevance to accounting's objectives of measuring and reporting information for decision-making, management of human resources, custodianship of human resources and social controls over the utilization of people. Thus, the model can potentially help enlarge the scope of accounting in accordance with the recommendations in A Statement of Basic Accounting Theory. There are, of course, some limitations involved in the model. First, the model's scope is restricted to the nature and determinants of an individual's value to an organization. Thus it should not be inferred that the model purports to explain the value of groups of people in formal organizations. Similarly, it should not be inferred that the model purports to fully explain the nature of an individual's value. Future research may find that other variables should be included or that present variables are unnecessary.